TRANSLATION METHODS ON TOURISM FLIGHT MAGAZINE FROM ENGLISH INTO BAHASA INDONESIA - Novia Tri Luwing (LPPM Universitas Dhyana Pura, 2023)
This study aims to analyze the translation methods found in flight magazine on GarudaIndonesia. Newmark (1988) divided the strategy of translation into procedure and method.the focused of this study only discuss method. this study used qualitative descriptive methodto analyze the data. The data used not participant interview. The source of the data was onflight magazine: colours (Garuda Indonesia, 2023). The data collected by Observation andnote taking from English language (SL) into Bahasa Indonesia (TL). The result showed thatthere were eight translation methods found on flight magazine, Word-for-word translation,Literal translation, Faithful translation, Adaptation translation, semantic translation, Freetranslation, Idiomatic translation, and Communicative translation. The most common methodfound in the data is Literal and Faithful translation.